If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -7(y + 1) = -10 + 4 Reorder the terms: 5 + -7(1 + y) = -10 + 4 5 + (1 * -7 + y * -7) = -10 + 4 5 + (-7 + -7y) = -10 + 4 Combine like terms: 5 + -7 = -2 -2 + -7y = -10 + 4 Combine like terms: -10 + 4 = -6 -2 + -7y = -6 Solving -2 + -7y = -6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -7y = -6 + 2 Combine like terms: -2 + 2 = 0 0 + -7y = -6 + 2 -7y = -6 + 2 Combine like terms: -6 + 2 = -4 -7y = -4 Divide each side by '-7'. y = 0.5714285714 Simplifying y = 0.5714285714
| 5y-8=6y+10 | | 30=-16t^2+40t+4 | | 5+3*4= | | 8.9X=16 | | 4x-(3x-7)=9 | | 56=5v+3v | | 6X+3+2x=11 | | 8x-12=50 | | x(squared)= | | 5c=8+4c | | 14y-5y=81 | | 6x+5+5x=93 | | 9x-2=7x+16 | | 46=4x+2x+10 | | (5/8)/(2/5) | | x(squared)+5= | | 0.75x+7=0.25x+3 | | (5i+2)(4-3i)-(2-i)(6i-7)=0 | | 9x+2=29x-2 | | 4(x-5)=7-17 | | 23-6x=-9x | | 7+5x+2x=42 | | 24x=13x-5 | | -20.3=6w+3 | | 8k+2=36k | | q/8/3 | | J/5-8=4 | | 2x+6+6x=30 | | 7(p-3)=4 | | 3/3/-1/3 | | u/4=52 | | 7a+44=-5 |